2016
DOI: 10.3390/ma9100811
|View full text |Cite
|
Sign up to set email alerts
|

µXRF Elemental Mapping of Bioresorbable Magnesium-Based Implants in Bone

Abstract: This study investigated the distribution of the elemental constituents of Mg-based implants at various stages of the degradation process in surrounding bone tissue, with a focus on magnesium (Mg), as the main component of the alloy, and yttrium (Y), due to its potential adverse health effects. The measurements were performed on the implant-bearing thin sections of rat bone in a time series of implant degradation between one and 18 months. Micro X-ray fluorescence analysis (μXRF) with a special spectrometer mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…By comparing the images of tissue around the implant to those of control tissue obtained from sham animals, the tissue-implant interaction can be analyzed. This can be done by observing the morphology, number and function of cells that were directly or indirectly in contact with the implant under an optical microscope, SEM, or confocal laser scanning microscope ( Figure 3a) [54][55][56]. The remnant of corrosion products can be viewed and measured in terms of size and distance from the implantation site ( Figure 3b) [57].…”
Section: Histological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the images of tissue around the implant to those of control tissue obtained from sham animals, the tissue-implant interaction can be analyzed. This can be done by observing the morphology, number and function of cells that were directly or indirectly in contact with the implant under an optical microscope, SEM, or confocal laser scanning microscope ( Figure 3a) [54][55][56]. The remnant of corrosion products can be viewed and measured in terms of size and distance from the implantation site ( Figure 3b) [57].…”
Section: Histological Analysismentioning
confidence: 99%
“…Example of local and systemic histological assessment of tissue-implant interaction: (a) fluorescence image of Villanueva stain on Mg alloy-contained femoral bone of New Zealand white rabbits after 26 weeks of implantation indicating a formation or differentiation of bone cells at the tissue-implant interface, which would not appear when using general stain of Hematoxillin-Eosine; (b) Micro X-ray Fluorescence (µXRF) elemental mapping of explanted WZ21 Mg alloy from femoral bone of a Sprague-Dawley rat after 12 months of implantation showing an elemental map that helps to understand the spreading of corrosion product in the vicinity of the implant; (c) Prussian blue stain image of liver, heart and spleen of mice after nine months of exposure to Fe stent implantation depicting corrosion product deposit in the organ of interest as a way of systemic evaluation of organs toxicity. Adapted with permission from John Wiley and Sons[55,56,58].…”
mentioning
confidence: 99%
“…62 It has also been demonstrated that the degradation of Y-containing alloy leads to the enrichment of Y concentration in the adjacent and newly formed bones. 63,64 However, the local Y-enrichment disappears with the complete degradation of the implant and bone remodeling with time. In this study, the lack of any detectable concentration of rare earth elements in the organs is possibly due to the very short duration of the study, and therefore, further studies will be required to demonstrate the complete absence of any systemic toxicity arising from this alloy.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The in-house-built µ-XRF spectrometer is specifically designed for the detection of a wide range of elements and its suitability for the analysis of biological samples has been demonstrated. 33,34 The instrument is equipped with a Rh-anode low power X-ray tube, and a Si(Li) detector (active area 30 mm 2 , LN 2 -cooled) with an ultrathin polymer window to allow the measurement of the low energy fluorescence radiation emitted by light elements. The primary beam was focused by a polycapillary optic (full lens) into a micro-beam with the size 50 × 50 µm 2 at Cu-Kα (determined using a standard test sample).…”
Section: µXrf Imagingmentioning
confidence: 99%